Gulupa fruit (Passiflora edulis Sims), its export potential, matrix and ripening signature: a review - DE ARMAS COSTA, RICARDO JOAQUÍN; Martín Gómez, Pedro Fernando; Rangel Díaz, Jorge Eliecer (Universidad Pedagógica y Tecnológica de Colombia, 2022)
A bibliographic review of the Gulupa fruit (Passiflora edulis Sims) was carried out on the following three topics. First on the scientific studies related to the export of these fruits from the municipalities or producing areas of the country to international markets; these studies show the potential of this agricultural business. Second on the scientific studies related to the processes and changes that occur in these fruits during the ripening stage such as, for example, the change in the coloration of the exterior of its epidermis and in the ripening variables (physical, chemical, volatile components, nutritional contents and respiratory intensities among others); studies that allow preserving and prolonging its shelf life during exports. Third, scientific studies related to the ripening matrix, the ripening signature of these fruits and their relationship with exports; concepts that allow the development of assistance tools for fruit producers, such as, for example, applications to determine their ripening status during harvest. It is hoped that the information gathered, organized and analyzed in this work will be of interest and value to the community interested in the agribusiness of gulupa exports as well as in the research of agroecosystems producing these fruits.